Endocannabinoids modulate human blood-brain barrier permeabilityin vitro - Hind, William H.; Tufarelli, Cristina; Neophytou, Maria; Anderson, Susan I.; England, Timothy J.; O'Sullivan, Saoirse (Wiley, 2015)
Background and Purpose